Valuing Simplicity: Developing a Good Point of Care Diagnostic - Engel, Nora; Krumeich, Anja (Frontiers in Sociology, 2020)
Point-of-care testing promises laboratory-based precision in settings that do not have easy access to laboratory-based diagnosis or where accessing a laboratory takes too long or is too costly. Developers and global health actors stress values and norms such as simplicity, rapidity and accuracy for realizing diagnostic innovations that work at point of care and are aligned to the specific requirements of point-of-care settings. This paper uses fieldwork among diagnostic manufacturers, scientists, donors, members of civil society, industry consultants, international organisations, regulators, policymakers, programme officers, lab technicians and clinicians involved in development and implementation of tuberculosis and HIV diagnostics, to examine how norms and values of what constitutes a good point-of-care diagnostic are operating in practice through both top-down and bottom-up dynamics. It draws the link between design, evidence and adoption of diagnostics and how the different actors interpret the values underpinning the new practice. The analysis draws on literature on valuation practices, evidence-making and technology design in science and technology studies and medical sociology. The results reveal how these values constitute innovation, implementation and evaluation practices across global and local (India) sites; for instance, how specific ideas of simplicity come to dominate over others and compete with value registers of accuracy, cost, workflow, biosafety or patient pathways, and how developers adjust their innovation and evaluation practices to competitors and gold standards. These particular practices and politics of valuing point-of-care diagnostics have consequences for design, accessibility and utilization of diagnostics. What is more, making a diagnostic work in local practices and workflows brings forward other priorities than diagnostic developers and global health actors usually expect, complicating ideas of simplicity, rapidity and accessibility and challenging global norms and valuation practices of what is considered a good diagnostic.